Information security awareness among students in eastern indonesia: A HAIS-Q based assessment and intervention priority mapping - Muhammad Fadlan; Syarifah Syarifah; Denis Prayogi; Suprianto Suprianto (SHM Publisher, 2026)
The increasing use of digital technology among university students is not always accompanied by adequate levels of information security awareness, especially in Eastern Indonesia, which has its own characteristics and challenges regarding facilities and digital literacy. This study aims to assess students’ information security awareness using an adapted HAIS-Q and to provide a soft computing-oriented interpretation for mapping intervention priorities. A quantitative survey was conducted involving students from Universitas Amal Ilmiah Yapis Wamena. The instrument measured three awareness dimensions, namely knowledge, attitude, and behaviour, across five focus areas. The results show that students’ information security awareness is generally in the good category, with attitude obtaining the highest score of 81.44, followed by knowledge at 80.10, and behaviour at 75.04. At the focus area level, mobile device security achieved the highest mean score, while email security obtained the lowest. The distribution of awareness levels shows that 60% of respondents were in the good category, 33% in the average category, and 7% in the poor category. From a soft computing perspective, these results can be interpreted as input indicators for mapping intervention priorities, particularly by identifying behaviour-related weaknesses, vulnerable awareness groups, and specific security domains requiring improvement.